Epigenetic Control of Endocrine Pancreas Differentiation in vitro: Current Knowledge and Future Perspectives - Astro, Veronica; Adamo, Antonio (Frontiers in Cell and Developmental Biology, 2018)
The raising worldwide prevalence of Type 1 and Type 2 diabetes mellitus (T1DM and T2DM) solicits the derivation of in vitro methods yielding mature and fully functional β-cells to be used in regenerative medicine. Several protocols to differentiate human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) into human pancreatic β-like cells have recently been developed. These methods, coupled with a bioengineering approach using biocompatible encapsulating devices, have recently led to clinic experimental clinical trials showing great promises to ultimately end the battle of diabetic patients for managing hyperglycemia. However, in vitro differentiation protocols face the challenge of achieving homogenous population of mono-hormonal insulin-secreting mature β−cells. Major epigenetic events such as DNA methylation, post-translational modification of histones and non-coding RNAs expression, orchestrate physiological endocrine pancreas specification into α−, β−, γ− and δ−cells, both in vivo and in vitro. The dysregulation of such epigenetic processes is associated to multiple pancreatic disorders including diabetes. Understanding the epigenomic and transcriptomic landscape underlying endocrine pancreas development could, therefore, improve in vitro differentiation methods. In this review, we summarize the most effective protocols for in vitro differentiation of hESCs/hiPSCs towards pancreatic β−cells and we discuss the current limitations in the derivation of functional glucose-responsive, insulin-releasing β−cells. Moreover, we focus on the main transcriptional and epigenetic events leading to pancreatic specification and on the applicative potential of novel epigenetic drugs for the establishment of innovative pharmacological therapeutic approaches.